The Economics of the Digital Services Tax - Wolfram F. Richter (Center for Economic Studies and ifo Institute (CESifo), 2019)
The use of digital services is largely non-rival. This paper argues that vanishing marginal costs of supply change policy incentives. Small countries are incentivized to tax the import of digital services. In fact, various countries have already moved towards expanded source taxation of online business activities. If such practice spreads, the quality of digital services will be negatively affected. This paper argues that countries exporting digital services have reason to respond by promoting an international tax regime in which the profit earned on remote supplies of digital business services is split between the countries involved.
Keywords: H25; M48; 330; digital services; remote supply; import tax; alleviating double taxation; profit splitting